Merger in Contests - Steffen Huck; Kai A. Konrad; Wieland Müller (Center for Economic Studies and ifo Institute (CESifo), 2000)
Competition in some markets is a contest. This paper studies the merger incentives in such markets. Merger can be profitable. The profitability depends on the post-merger contest st ructure, the discriminatory power of the contest and on the number of contestants
Keywords: 330; Contests; merger